Is EPCR a multi-ligand receptor? Pros and cons - Montes, Ramón; Puy, Cristina; Molina, Eva; Hermida, José (Thrombosis and Haemostasis, 2012)
In the last decade, the endothelial cell protein C/activated protein C receptor (EPCR) has received considerable attention. The role initially attributed to EPCR, i.e. the enhancement of protein C (PC) activation by the thrombin-thrombomodulin complex on the surface of the large vessels, although important, did not go beyond the haemostasis scenario. However, the discovery of the cytoprotective, anti-inflammatory and anti-apoptotic features of the activated PC (APC) and the required involvement of EPCR for APC to exert such actions did place the receptor in a privileged position in the crosstalk between coagulation and inflammation. The last five years have shown that PC/APC are not the only molecules able to interact with EPCR. Factor VII/VIIa (FVII/VIIa) and factor Xa (FXa), two other serine proteases that play a central role in haemostasis and are also involved in signalling processes influencing wound healing, tissue remodelling, inflammation or metastasis, have been reported to bind to EPCR. These observations have paved the way for an exploration of unsuspected new roles for the receptor. This review aims to offer a new image of EPCR in the light of its extended panel of ligands. A brief update of what is known about the APC-evoked EPCR-dependent cell signalling mechanisms is provided, but special care has been taken to assemble all the information available about the interaction of EPCR with FVII/VIIa and FXa.
Keywords: EPCR; protein C; factor VII; factor X; endothelium